Determinants for inappropriate initiation of complementary feeding to children aged 6-24 months in Gondar Health Centers, Northwest Ethiopia, 2019 - Kassahun Gebeyehu Yazew; Abebaw Alemayehu Desta (Elsevier, 2021)
Background: The practice of the timely initiation of complementary feeding is serious for the achievement of healthy advancement and progress. The timely initiation complementary feeding practice failure was the main leading issues of the under nutrition. Objective: To assess timely initiation of complementary feeding practice and associated factors to children aged 6-24 months at Gondar town Health institutions, Northwest Ethiopia, 2019. Methods: An institution-based cross- sectional study was conducted from May 01 to 30/2019. A sample of 381 subjects, were selected by using systematic random sampling technique. Data were collected using pre-tested interviewer-administered structured and semi-structured questionnaires. The data were cleaned, coded, entered in to EPI-INFO version 7, and transferred and analyzed using SPSS version 21. Results: Out of 381 study participants, 252 (66.1%) had initiated complementary feeding practices to their children timely. Mothers' grade level one up to eight [AOR = 2.26], antenatal care visit greater than or equal to three times [AOR = 1.85], number of children two up to four [AOR = 2.30], family size four up to six [AOR = 1.79], and knowledgeable mothers [AOR = 1.98] times were positively associated with timely initiation of complementary feeding practices. Conclusions: Timely initiation of complementary feeding practice was more than three among five participants (i.e. 252 (66.1%)). Mothers' educational level, number of children, antenatal care visit, family size and mothers' knowledge were the main factors for the timely initiation of complementary feeding.